Synthesis of PtxPdy nanoparticles decorated functionalized carbon nanotubes as highly anodic catalysts for formic acid fuel cells - Suwaphid Themsirimongkon (2018)
© 2015 The Authors. PtxPdy catalysts with various compositions onto functionalized carbon nanotubes (CNTs) were prepared by improved polyol method to study their electrocatalytic activities toward a formic acid oxidation. Carbon nanotubes as supports (CNTs) were functionalized by acid solutions and the different atomic weight ratios of Pt to Pd supported the functionalized CNTs were prepared. X-ray diffraction (XRD) and transmission electron microscopy (TEM) were used to investigate the catalyst morphologies and particle size distributions. A uniform dispersion of alloyed microstructure PtxPdy particles with diameters ranging between 2-4 nm was obtained. The effect of different surface compositions of various PtxPdy /CNTs alloy particles on electrocatalytic formic acid oxidation were investigated by cyclic voltammetry (CV) and chronoamperometry (CA). The results showed an excellent activities and stabilities which are indicated by its lower onset potential and higher current density. Moreover, the PdPt/CNTs catalyst was obtained higher superior electrocatalytic activity than the other PtxPdy catalysts and the commercial PtRu/C.